Pengaruh Fungsi Badan Pengawas, Kualitas Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pada Lembaga Perkreditan Desa Se- Kota Denpasar - Ni Putu Mariani; Ni Wayan Yuniasih; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2023)
Quality financial reports are very important for LPD to be able to assist in making decisions regarding their operations. This study intend to determine the function of the supervisory agency, the quality of human resources and the use of information technology on the quality of financial reports. The population in this study were 175 employees in 35 LPDs in Denpasar City, consisting of the LPD Chair, Secretary, and Supervisory Agency. The sampling technique in this study used is jenuh sampling method. The results showed that the variables of the function of the supervisory agency, the quality of human resources and the use of information technology had a significant positive effect on the quality of financial reports at the Village Financial Institutions (LPD) City. Keyword: The Influence of Supervisory Agency, Quality of Human Resources and Information Technology on Quality Financial Reports.